Could anti-HCV treatment prevent recurrence of hepatocellular carcinoma in HIV-infected patients? Two case reports - Cenderello, G.; Pontali, E.; Cassola, G.; Torresin, A. (Infection, 2013)
Highly active antiretroviral therapy (HAART) has proven long-term efficacy in human immunodeficiency virus (HIV) infection. Combination therapy with pegylated interferon and ribavirin has become the standard of care in patients with both hepatitis C virus (HCV) chronic hepatitis and HIV/HCV co-infection. Data on the safety and efficacy of combination therapy in chronic hepatitis C patients with hepatocellular carcinoma (HCC) is scarce and even more so in HIV/HCV co-infected subjects. We report the successful administration of both HAART and anti-HCV therapies in two HIV/HCV co-infected patients after HCC eradication. These encouraging results might argue for the feasibility of an aggressive approach in the management of co-infected patients with HCC.